2014
DOI: 10.1111/jjns.12058
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate nursing students' perceptions about disaster preparedness and response in Istanbul, Turkey, and Miyazaki, Japan: A cross‐sectional study

Abstract: Disaster characteristics were not described by one third of the students. Of the two-thirds that were described, most were of events that were highly predictable because of their frequencies in the given areas. Universities need to target and then focus on high-risk factors in their areas and have disaster plans for students who can provide triage and managerial nursing roles as disaster responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…The literature provides evidence for these findings such as research by Nofal, Alfayyad, Khan, Al Aseri, and Abu‐Shaheen () which indicated that education develops the individual necessary knowledge related to the disaster emergency preparedness, which further highlights its need. Öztekin, Larson, Yüksel, and Altun Uğraş () also stated that maturation of the students’ knowledge related to disasters preparedness develops through increased education. For example, a nursing curriculum may instigate the necessary clinical skills of assessing, planning, implementing and evaluating the individual needs in the disaster situation.…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides evidence for these findings such as research by Nofal, Alfayyad, Khan, Al Aseri, and Abu‐Shaheen () which indicated that education develops the individual necessary knowledge related to the disaster emergency preparedness, which further highlights its need. Öztekin, Larson, Yüksel, and Altun Uğraş () also stated that maturation of the students’ knowledge related to disasters preparedness develops through increased education. For example, a nursing curriculum may instigate the necessary clinical skills of assessing, planning, implementing and evaluating the individual needs in the disaster situation.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses, whose competencies have developed, usually have increased beliefs that they are well prepared for a disaster and along with this their confidence in disaster response is known to increase, as well (Park & Kim, 2017). Nurses are highly motivated to participate in disaster response but are not entirely sure of their roles (Oztekin, Larson, Yüksek, & Altun Uğraş, 2015;Peoples, Gebbie, & Hutton, 2016). Also, student nurses reported that they did not have the necessary knowledge and skills to respond to disasters and that training on disaster management would improve their knowledge and skills and increase their beliefs (Grimes, Sparke, Rouen, & West, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…재난은 자연이나 인간이 만들어 낸 영향력이 지역사회의 능력을 넘어서는 상태로써 재난과 관련된 특별한 건강관리 요구를 만들어 내고 사회 뿐만 아니라 재난관리 인력인 간호 사와 간호대학생은 간호사를 재난관리에 중요인력으로 인식 되고 있다 (Lee I et al, 2003;Öztekin et al, 2015). 최 근의 재난 발생 형태와 문제를 볼 때 간호사는 전통적인 간 호사의 재난관리 활동 뿐만 아니라 좀 더 전문적이고 효율적 인 활동을 위해 재난에 대비하기 위한 지식과 기술을 갖추어 야 하며 자발적이며 적극적인 자세로 재난관리에 임해야 한 다.…”
unclassified